EVALUASI SIFAT PREBIOTIK SERAT PANGAN TIDAK LARUT AIR (STLA) TEREKSTRAK DARI TEPUNG BUAH PISANG AGUNG DAN PISANG MAS - Nurhayati Nurhayati; Ahmad Nafi'; Yulita Nur Pratiwi (Faculty of Agricultural Technology, University of Jember, 2015)
Bananas have potential to be developed as a functional food prebiotic because it contains a resistant starch and dietary fiber. The raw banana contains 50% of resistant starch type II and 14.52% of dietary fiber. The aim of the research was to evaluate prebiotic properties insoluble dietary fiber (IDF) extracted from agung and mas banana flour. The banana flour produced from agung and mas variety used controlled fermentation by Brevibacillus brevis for 24 hours at room temperature. The IDF was extracted by using enzyme method. The prebiotic properties were evaluated based on their resistance to gastric acid hydrolysis, their capable to increase survival of probiotic bacteria (Lactobacillus acidophilus) and decrease pathogenic bacteria (enteropathogenic Eschericia coli/EPEC). The results showed that process fermentation of banana flour increased IDF content of mas and agung banana flour. The IDF of fermented mas and agung banana flour were more resistant than non-fermented mas and agung banana flour by hydrolysis gastric acid and increase the survival of L. acidophilus, but decreased the survival of EPEC.Keywords: banana, insoluble dietary fiber, prebiotic properties